Trends, Methods And Thinking In Contemporary Management – Analysis And Benefits For Improving The Effectiveness Of Management - Tóth, Endre (Communication Today, 2025)
There are currently numerous management methods and their number is still growing. With this tendency the problem of monitoring, perception and adoption grows as well. Identifying and supporting contemporary search is therefore current both in theoretical and practical spheres. This paper focuses on identiﬁcation of trends in management that can be (on the current level of knowledge) regarded as the most modern and perspective. Such trends are process management, direction of bionic and holistic thinking, ﬁnding performance excellence and prominence, computerization and technology management. Individual movements are characterized by the most prominent representative methods, especially in terms of their functional utility for managers. The interpretation also provides a conceptual evaluation of advantages and disadvantages of the most important methods and their perspective is outlined in the current crisis and turbulent conditions of globalized economy.